Identification of Aedes Breeding in High-Rise Buildings Element: A Case of Lembah Pantai - Zainon, N.; Mohd-Rahim, F.A.; Abd-Karim, S.B. (University of Malaya, 2015)
Dengue cases that have been reported worldwide were related with high rise buildings especially in residential buildings such as apartments and condominiums. This report has produced with the aim to study the identification of the Aedes breeding areas resulted from building designs. Subsequently, possible solutions were put forward, based on the current construction technology that is already available on the market. This report represents empirical findings of common Aedes breeding spots on high-rise buildings. We found commonalities in building elements that act as a catalysts for Aedes breeding. Of special interest, however, is the emergence of a new factor of the uneven flat floors and rooftop in relation to the Malaysia where this factor is unique to our country, and issue for further research. There are two main potential implications of this research. Firstly, our building designs are not at fault, but it seeks the application of construction technologies. Preventing Aedes should start and involve the whole lifecycle of building, construction, and projects. Secondly, the building also requires maintenance. Therefore, the need for maintenance will only intensify in the effort of curbing dengue cases. Frequent cleaning of water ponding in any building elements should be conducted to ensure a healthy environment free from dengue. Findings from this study is a part of the fundamental input for ongoing research project undertaken by the Department of Quantity Surveying, Faculty of Built Environment, University Malaya, in cooperation with the Dengue Coalition Council. Copyright@ 2014 University of Malaya all right reserved